Evidence of a bacterial core in the stored products pest Plodia interpunctella: the influence of different diets. (1st August 2016) - Montagna, Matteo; Mereghetti, Valeria; Gargari, Giorgio; Guglielmetti, Simone; Faoro, Franco; Lozzia, Giuseppe; Locatelli, Daria; Limonta, Lidia
Summary: The potential influence of insects' feeding behaviour on their associated bacterial communities is currently a matter of debate. Using the major pest of commodities, Plodia interpunctella, as a model and adopting a culture‐independent approach, the impact of different diets on the host‐associated microbiota was evaluated. An analysis of similarity showed differences among the microbiotas of moths fed with five substrates and provided evidence that diet represents the only tested factor that explains this dissimilarity. Bacteria shared between food and insects provide evidence for a limited conveyance to the host of the bacteria derived from the diet; more likely, the content of carbohydrates and proteins in the diets promotes changes in the insect's microbiota. Moth microbiotas were characterized by two robust entomotypes, respectively, associated with a carbohydrate‐rich diet and a protein‐rich diet. These results were also confirmed by the predicted metagenome functional potential. A core microbiota, composed of six taxa, was shared between eggs and adults, regardless of the origin of the population. Finally, the identification of possible human and animal pathogens on chili and associated with the moths that feed on it highlights the possibility that these bacteria may be conveyed by moth frass.